Firm's cooperation activities: The relevance of public research, proximity and personal ties - A study of technology-oriented firms in East Germany - Charlotte Schlump; Thomas Brenner (Philipps-University Marburg, Department of Geography, 2013)
Cooperation in innovation processes has become crucial for the competitiveness of many firms. This paper focuses on technology-oriented East German firms and analyses details of their cooperation behaviour by studying the relationships between geographic and social proximity, the importance and frequency of cooperative interaction and the attributes of innovation cooperation partners that influence the importance of cooperation. Data is collected in two questionnaires and analysed by regressions. It is found, among other results, that cooperation that is established via personal contacts is, on average, more helpful and important for firms but involves less frequent interaction.
Keywords: D20; I28; O32; R11; 330; cooperation; firm; East Germany; policy